2010
DOI: 10.1177/0272989x10369008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Adding a Values Clarification Exercise to a Decision Aid on Heart Disease Prevention: A Randomized Trial

Abstract: Background Experts have called for the inclusion of values clarification (VC) exercises in decision aids (DA) as a means of improving their effectiveness, but little research has examined the effects of such exercises. Objective To determine whether adding a VC exercise to a DA on heart disease prevention improves decision making outcomes. Design Randomized trial. Setting UNC Decision Support Laboratory. Patients Adults ages 40–80 with no history of cardiovascular disease. Intervention A web-based he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 19 publications
(29 reference statements)
1
45
0
1
Order By: Relevance
“…Investigators pilot-tested a previous version of the decision aid [26] and studied its effects with and without the values clarification section [25]. The coaching portion has not been independently described or tested; a more detailed description is provided in Additional File 1.…”
Section: Methodsmentioning
confidence: 99%
“…Investigators pilot-tested a previous version of the decision aid [26] and studied its effects with and without the values clarification section [25]. The coaching portion has not been independently described or tested; a more detailed description is provided in Additional File 1.…”
Section: Methodsmentioning
confidence: 99%
“…More recent studies found that explicit VCEs lead to more satisfaction with preparation for decision making [26] and lower decisional conflict [27]. However, some studies did not find significant improvements in decision making when adding an explicit VCE to a DA [28].…”
Section: Values Clarification Exercisementioning
confidence: 99%
“…The Science Panel on Interactive Communication and Health noted the benefits of interactive elements in health communication by helping individuals better understand their health-related values and decisions in an engaging way [42]. Though a recent paper has found no direct benefit of using a values clarification tool for heart disease-related decision making [43], several recent studies in cancer-related decision making have found that both breast cancer and PCa patients have better outcomes, such as less decisional conflict, when using media with interactive elements versus informational materials with no interactivity [28,[31][32][33]. Additionally, a recent paper assessing participants' use of a web-based smoking cessation tool found that increased use of interactive website features and more frequent use of the website contributed to sustained smoking cessation [34].…”
Section: Original Researchmentioning
confidence: 99%